OPTIMIZATION OF PASSPORT ISSUANCE RULES FOR PROSPECTIVE INDONESIAN MIGRANT WORKERS IN THE FORMAL SECTOR (CASE STUDY IN CLASS I IMMIGRATION OFFICE NON TPI TANGERANG) - Dino Fahrenzky; Anita Herlina (Jurnal Ilmiah Kajian Keimigrasian, 2021)
ABSTRAK Banyaknya pengangguran di wilayah Tangerang serta diiringi oleh tingginya permintaan pekerja Migran Indonesia dari negara yang memiliki kontrak kerjasama dengan negara Indonesia sehingga masyarakat bersedia menjadi PMI dengan tujuan agar mendapatkan kehdupan yang lebih baik. Jenis Pekerja Migran Indonesia pada sektor formal yang digolongkan kedalam jenis Pekerja Migran Indonesia yang bekerja pada pemberi kerja yang berbadan hukum. Aturan yang mengatur tentang persyaratan penerbitan paspor bagi calon pekerja migran Indonesia diatur dalam Peraturan Menteri Hukum dan Hak Asasi Manusia Nomor 8 Tahun 2014 tentang Paspor Biasa dan Surat Perjalanan Laksana Paspor. Surat Rekomendasi penerbitan paspor dari Dinas Ketenagakerjaan sebagaimana merupakan salah satu syarat penerbitan paspor bagi calon pekerja migran Indonesia, namun dalam implementasinya di Kantor Imigrasi Kelas I Non TPI Tangerang calon pekerja migran Indonesia khususnya pada sektor formal sering tidak mengurus penerbitan surat rekomenasi penerbitan paspor dari Dinas Ketenagakerjaan karena berbagai alasan. Oleh karena itu dijelaskan implementasi peraturan terhadap calon PMI yang mendaftarkan penerbitan paspor di Kantor Imigrasi Kelas I Non TPI Tangerang apakah aturan terhadap calon PMI sektor formal tersebut sudah optimal. Sehingga perlu adanya optimalisasi terhadap aturan yang mengatur tentang persyaratan penerbitan paspor bagi calon pekerja migran Indonesia khususnya pada sektor formal yang belum optimal. Hal ini dilihat dari sistem keimigrasian pada saat entry data hanya calon pekerja migran sektor informal saja yang diwajibkan menginput ID PMI sedangkan untuk calon pekerja migran Indonesia pada sektor formal tidak menginput ID PMI sehingga proses entry data bisa dilanjutkan. Maka urgensi dari surat rekomendasi penerbitan paspor dari Dinas Ketenagakerjaan hanya difokuskan kepada calon pekerja migran Indonesia pada sektor informal saja tidak terhadap calon pekerja migran Indonesia sektor formal. Kata Kunci: optimalisasi, aturan, pekerja migran Indonesia, formal ABSTRACT The high number of unemployed in the Tangerang area and accompanied by the high demand for Indonesian Migrant workers from countries that have a cooperation contract with the Indonesian state so that people are willing to become PMI with the aim of getting a better life. Types of Indonesian Migrant Workers in the formal sector are classified into the types of Indonesian Migrant Workers who work for employers who are legal entities. The rules governing passport issuance requirements for prospective Indonesian migrant workers are regulated in the Minister of Law and Human Rights Regulation Number 8 of 2014 concerning Ordinary Passports and Travel Letters Like Passports. Recommendation letter for issuing passports from the Manpower Office as one of the requirements for issuing passports for prospective Indonesian migrant workers, but in its implementation at the Immigration Office Class I Non TPI Tangerang prospective Indonesian migrant workers, especially in the formal sector, often do not take care of issuing recommendation letters for issuing passports from the Manpower Office for various reasons. Therefore, it is explained that the implementation of regulations for PMI candidates who register for passport issuance at the Class I Non-TPI Tangerang Immigration Office is explained whether the rules for PMI candidates in the formal sector are optimal. Therefore, it is necessary to optimize the rules governing the requirements for issuing passports for prospective Indonesian migrant workers, especially in the formal sector which is not yet optimal. This can be seen from the immigration system at the time of data entry, only prospective migrant workers in the informal sector are required to input PMI ID, while prospective Indonesian migrant workers in the formal sector do not enter PMI ID so that the data entry process can continue. Therefore, urgency of the recommendation letter for passport issuance from the Manpower Office is only focused on prospective Indonesian migrant workers in the informal sector, not on prospective Indonesian migrant workers in the formal sector. Keywords: optimization, regulation, Indonesian Migrant Workers, formal